The macro-economic impact of e-commerce in the EU Digital Single Market - Melisande Cardona; Néstor Duch-Brown; Joseph Francois; Bertin Martens; Fan Yang (European Commission, Joint Research Centre (JRC), 2015)
This paper examines the economic impact of a change in retail technology - the shift from offline to online shopping – and a change in policy – measures to reduce the barriers to online trade perceived by consumers and retailers. Contrary to the prevalent micro-economic partial equilibrium consumer modelling approach to e-commerce, we use a macro-economic general equilibrium model that brings together the impact on consumers as well as on producers. We use survey data on cross-border e-commerce between EU Member States to estimate the implied cross-border trade cost reduction when consumers move from offline to online consumption as well as the implied costs of perceived regulatory barriers to e-commerce. We distinguish between cross-border and domestic trade costs effects. We find that cross-bordere-commerce reduces trade costs compared to offline trade. Increased price competition squeezes domestic retail price margins and has a negative output effect in that sector (-2.6%). However, the resulting retail efficiency gains have a positive effect on production in other sectors (between 0.9 and 2.6%) and on household consumption (+1.07%). The combined macro-economic effect of these transmission channels adds 0.14% to EU GDP. Additional policy measures to facilitate cross-border e-commerce between EU Member States could add another 0.3% to household consumption and 0.04% to GDP, or 0.03% in the more conservative estimate. The relatively weak GDP effect in comparison with the production and consumption effects indicates that the shift from offline to online retail induces considerable welfare redistribution from retailing to other sectors and to households, more so than a production effect.
Keywords: F14; F47; 330; e-commerce; online trade; cross-border trade; international online trade; trade costs; trade barriers